Derajat keparahan infeksi Soil Transmitted Helminths terhadap status gizi dan anemia pada anak sekolah dasar - Farissa Fatimah; Sri Sumarni; Muhammad Juffrie (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2012)
Backgound: Indonesia as a tropical country with high humidity, has good environment for worm breeding particularly Soil Transmitted Helminths (STH). The prevalence of worm infestation in Indonesia is still relatively high, about 60% of 220 million Indonesian population, 21% of them are elementary school-age children. STH intensity greatly affects the nutritional status of patients, in wich more severe infection leads to poorer nutrition condition.Objective: To identify severity of STH infection in elementary school student at the working area of Kokap I Health Center of Kulonprogo and its correlation with nutritional status and anemia.Method: The study was undertaken in 25 elementary schools at the working area of Kokap I Health Center of Kulonprogo. Samples were all students of grade I as many as 241 students. Worm examination was done by using Kato-Katz method, assessment of nutrition status was based on body weight according to height (weight/height), anemia status was assessed from Hb level using Cyanmethaemoglobin method.Results: The results of the study showed that most of students (83,6%) were well nourished and were non anemic (84,9%). No student belonged to severe anemic category, 3 students (1,3%) had anemia at medium category and 31 students (13,8%) were slightly anemic. Out of 51 students that positively got STH infection, 16 students (31.4%) had light infection of A. lumbricoides, 36 students (70,6%) had T. trichiura and 4 students (5,9%) had hookworm. A. lumbricoides infected 7 student (13,7%) and T. trichiura infected 8 student (15,7%) both at medium criteria. There was no infection at severe criteria. The result of Somers’ D analysis showed that there was no significant correlation between the two variables (p>0,05).Conclusion: There was no correlation between severity of STH infections with nutrition status and anemia in elementary school student.